Proteomic profiling of Labeo rohita intestine infected with Edwardsiella tarda: Unveiling the mucosal defense mechanisms, cell adhesion, and cytoskeletal pathways - Nevil Pinto; Mehar Un Nissa; Gowhar Iqbal; Yashwanth BS; Darshan P; Sanjeeva S; Mukunda Goswami (Comparative Immunology Reports)
Introduction: The pathogenicity mechanism of the intestine induced by the enteric bacteria Edwardsiella tarda is essential for global aquaculture. The fish intestine is vital for immunological response, nutrition absorption, osmoregulation, and environmental interactions. Proteomics is a valuable technique in aquaculture research to better understand fish intestinal physiology, health, and disease. Method: In our study, Labeo rohita was infected with Edwardsiella tarda for 48 h. Histopathology was performed to overview changes in rohu intestine. Label-free quantitative proteomic analysis of the rohu intestine was performed to elucidate the proteome changes and its implications for immune response. Gene ontology and protein-protein interactions were predicted for differentially abundant proteins (DAPs) using Metascape and ShinyGo web tools. Results: In DAPs, 50 proteins were identified as highly abundant, while 32 were identified as lower abundant. In E. tarda infected intestine, protein pathways were involved in defense response to the bacterium (muc-2), pyruvate metabolism (ldhb), integrin-mediated cell adhesion (ilk), actin filament bundle (lcp1), and collagen-containing extracellular matrix (nid2a). The control group mapped to pathways; innate immune system (mhc), carbon metabolism (rgn), and regulation of body fluid levels (fgg). Major intestinal mucosal proteins intl-2, lgals3, fucolectin, prdx4, a2ml, cmpk1, and wap65 were among the DAPs for E. tarda infection. In the infected rohu, crp7 and col7a1 were related to intestinal homeostasis. The reduction in the metabolic and immune pathways of affected rohu intestine mechanisms evoked by E. tarda is critical to the pathogenesis of infection. Conclusion: Our study directly points to the possible disease biomarkers involved in cell adhesion, cytoskeleton rearrangement, and mucosal defense in the rohu intestine after Edwardsiellosis. The identified proteome of the rohu intestine could be used as a reference to establish their mechanism of action during bacterial infection that may contribute to the strategies against bacterial prevention in aquaculture.